The impact of an articulate storyline on students' cognitive learning outcomes in mathematics at Muhammadiyah Mertosanan Elementary School - Anggara , Yoga; Mardati, Asih (Jurnal Fundadikdas (Fundamental Pendidikan Dasar), 2025)
The integration of digital media in elementary education is increasingly recognized as an effective approach to addressing students’ learning difficulties. This study explores the impact of Articulate Storyline, an interactive multimedia platform, on the mathematics learning outcomes of third-grade students at Muhammadiyah Mertosanan Elementary School. The research was motivated by the challenge that many students scored below the minimum mastery criterion, highlighting the need for innovative instructional strategies to enhance comprehension and engagement in mathematics. A quasi-experimental design with pretest–posttest control groups was applied to compare the effectiveness of conventional teaching methods with those supported by Articulate Storyline. Data were collected primarily through pretests and posttests, supplemented by classroom observations. Statistical analyses confirmed that the experimental group, which learned with Articulate Storyline, achieved significantly higher posttest scores than the control group. Beyond numerical improvement, classroom observations also indicated increased student enthusiasm and active participation during the lessons supported by interactive media. The findings demonstrate that Articulate Storyline not only improves students’ cognitive achievement in mathematics but also fosters a more engaging learning environment. This highlights its dual function as both a learning aid and a motivational tool, aligning with contemporary efforts to integrate technology into primary education. The novelty of this study lies in providing empirical evidence on the application of Articulate Storyline in the context of elementary mathematics learning in Indonesia, an area that remains underexplored. Practically, the results suggest that teachers can adopt interactive multimedia platforms as complementary tools to enrich mathematics instruction, improve student performance, and stimulate greater classroom engagement.